2015
DOI: 10.1021/jacs.5b03948
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Oriented Growth of Surface-Attached Metal–Organic Frameworks: Surface Functionality, Deposition Temperature, and First Layer Order

Abstract: The layer-by-layer growth of a surface-attached metal-organic framework (SURMOF), [Cu2(F4bdc)2(dabco)] (F4bdc = tetrafluorobenzene-1,4-dicarboxylate and dabco = 1,4-diazabicyclo-[2.2.2]octane), on carboxylate- and pyridine-terminated surfaces has been investigated by various surface characterization techniques. Particular attention was paid to the dependency of the crystal orientation and morphology on surface functionality, deposition temperature, and first layer order. For the fully oriented deposition of SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
120
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(125 citation statements)
references
References 56 publications
5
120
0
Order By: Relevance
“…Surface‐anchored films of metal‐organic frameworks (SURMOFs) can be synthesized in a straightforward manner by using a liquid phase layer‐by‐layer (LbL) synthesis approach 8, 9. The benefits of this method include the growth of highly homogeneous and oriented films at room temperature,8, 10 with diverse topologies,11, 12 enabling at the same time controlled mechanistic studies of MOF assembly13, 14 and guest‐induced framework changes 15, 16, 17…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Surface‐anchored films of metal‐organic frameworks (SURMOFs) can be synthesized in a straightforward manner by using a liquid phase layer‐by‐layer (LbL) synthesis approach 8, 9. The benefits of this method include the growth of highly homogeneous and oriented films at room temperature,8, 10 with diverse topologies,11, 12 enabling at the same time controlled mechanistic studies of MOF assembly13, 14 and guest‐induced framework changes 15, 16, 17…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, alternately immersing the SAM/Au substrates in separate metal and linker solutions, with solvent washing steps in between, assures controlled growth. Resulting SURMOF orientation is dictated by the terminating groups of the SAMs 14, 18, 19. The most studied example of a SURMOF is [Cu 3 (btc) 2 (H 2 O) n ], commonly known as HKUST‐1, which typically includes copper acetate (Cu(CH 3 COO) 2 , abbreviated here as CuAc 2 ) and 1,3,5‐benzenetricarboxylate (btc) as precursors 8, 20…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that the growth of HKUST-1 on –COOH-terminated triptycene (Trp)-based SAMs proceeds along a different crystallographic axis than the growth on SAMs with a higher surface density of –COOH-functions, indicating that the surface density of –COOH units is a factor to liquid phase epitaxy of SURMOFs [20]. The temperature has another crucial impact on the efficiency and the direction of MOF growth on surfaces [3,21]. The strength of the chalcogenate–gold bond represents an upper limit to the MOF deposition temperature.…”
Section: Introductionmentioning
confidence: 99%